Predictors of long-acting contraceptive utilization hot spots in Ethiopia: using geographical weighted regression analysis - Abate, Hailemichael Kindie; Azagew, Abere Woretaw; Kassahun, Chanyalew Worku; Wassie, Mulugeta; Mekonnen, Chilot Kassa; Wassie, Yilkal Abebaw; Zegeye, Alebachew Ferede (Frontiers in Global Women's Health, 2024)
The use of long-acting contraceptives is a common health challenge in Ethiopia. Therefore, the current study aimed to assess the determinants of using long-acting contraceptive hotspots in Ethiopia using data from the Ethiopian Mini Demographic and Health Survey for 2019.This study used data from the Ethiopia Mini Demographic and Health Survey 2019 and included a total weighted sample of 8,885 women in the analysis. The geographical variation of longacting contraceptive usage was initially observed using hotspot analysis. Arc-GIS version 10.7 was used for geographically weighted regression. Ordinarily, least squares regression was performed to identify predictors that explain the geographical variation in the use of long-acting contraceptives. Geographic weighted regression was used to predict the hotspot area of longacting contraceptive methods.The overall prevalence of long-acting contraceptive utilization use was 6.9 %( 95% CI; (6.4-7.45). Most of the statistically significant hotspots for long-acting contraceptives were found in lactated areas of the Oromia part of Amhara and Dire Dawa. Primary education, followers of Muslim religion, married status, and women having >4 children were the determinants of spatial variation use of hotspot areas for long-acting contraceptive methods.Conclusions: Spatial analysis showed that primary education, followers of the Muslim religion, married status, and women having>4 children were the predictors of hotspot areas of the use of long-acting contraceptive methods. A detailed map of long-acting contraceptive use hotspots and their determinants will enable decisions to target their socio-demographic related predictors of the women.